Efektivitas Penggunaan Wordwall Sebagai Media Pembelajaran dalam Meningkatkan Keaktifan Siswa Kelas III Sekolah Dasar - Endah, Suci Nur; Falah, Irfan Fajrul (Indo-MathEdu Intellectuals Journal, 2025)
The background of this research is based on the still low activity of students in the teaching and learning process of Civics (PKn), which is suspected to be caused by the use of monotonous learning methods. The main objective of this study is to determine the effectiveness of using Wordwall learning media in increasing student activity in the Civics subject (PKn) in grade III of elementary school. This research employs a quantitative approach with a quasi-experimental design, involving 36 third-grade students as research subjects. Data were obtained through observations and questionnaires to assess student activity before and after the implementation of Wordwall. The data analysis technique used is the t-test. The research results indicate a difference in student learning activity, as seen from the difference in the experimental class questionnaire, which reached 82%, while the control class was only 68%. This research is expected to provide solutions for educators in creating interactive learning and increasing student learning activity.